2017
DOI: 10.1002/nau.23432
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing long‐term adherence to pelvic floor exercises in women with urinary incontinence

Abstract: Background and Objectives To ensure the effectiveness of Physical Therapy for urinary incontinence (UI), it is crucial that patients adhere to treatment in both the long and the short term. Treatment adherence may prevent symptom progression and the need for surgery, which is associated with higher costs and potential complications. Adherence is defined as carrying out a recommended behavioral modification or change. The World Health Organization (WHO) has established that adherence is a multifactorial phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Data extracted were: age of participants, setting of intervention, risk factors, or chronic diseases, the method used to measure PA, PAP treatments, and PAP adherence, theories related to human behavior change, score of mentioned PAP adherence factors according to the WHO fivedimensional adherence model (WHO, 2003). All adherence-related factors are described in Table 1 and proposed by other authors in the scientific literature (Conraads et al, 2012;Venegas et al, 2018;WHO, 2003). Modified RATS review guidelines were used for this critical literature review, with more than five points (10 points Likert-type scale) for the following points: relevance of study question (regarding the quality in the research question/aim of the study?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data extracted were: age of participants, setting of intervention, risk factors, or chronic diseases, the method used to measure PA, PAP treatments, and PAP adherence, theories related to human behavior change, score of mentioned PAP adherence factors according to the WHO fivedimensional adherence model (WHO, 2003). All adherence-related factors are described in Table 1 and proposed by other authors in the scientific literature (Conraads et al, 2012;Venegas et al, 2018;WHO, 2003). Modified RATS review guidelines were used for this critical literature review, with more than five points (10 points Likert-type scale) for the following points: relevance of study question (regarding the quality in the research question/aim of the study?…”
Section: Methodsmentioning
confidence: 99%
“…Blackstock et al proposed the WHO model to measure non-adherence to both pharmacological and non-pharmacological treatments in Chronic Obstructive Pulmonary Disease patients (Blackstock et al, 2016;WHO, 2003). Recently, Venegas, et al used the model to analyze the influencing factors in long-term adherence to physical therapy for women with urinary incontinence (Venegas et al, 2018). In a similar way, Conraads et al used it with heart failure patients in 2012.…”
Section: Uk (Burgosmentioning
confidence: 99%
See 1 more Smart Citation
“…Some earlier studies 2,3 have shown, as here, that continued adherence to exercise is the main factor in maintaining continence posttintervention. Feeling motivated to perform the exercises and committed to do so have been identified as significant factors in adherence 16 but here it was not practical to measure factors hypothesized to be associated with higher adherence: we cannot contribute to a discussion of whether, for example, those who continued exercise postintervention had higher expectations of self‐efficacy than those who did not 17‐19 . We cannot comment with any confidence either on the potential efficacy of continued group classes postintervention.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, Desveaux et al proposed a questionnaire to find facilitators and barriers of patients and HC providers in regard to a community-based exercise program [ 29 ], in a similar way than Myles et al, in Canada [ 36 ], Bock et al, in Germany [ 30 ], Freene et al, in Austalia [ 35 ], and Oyeyemi et al, in Nigeria [ 37 ]. Trying to filling in the gap, we propose a new validated questionnaire for analyzing feasibility of PAP in HC settings considering all dimensions and their respective integrated factors, according to the WHO 5 dimensions adherence model [ 16 , 42 ].…”
Section: Discussionmentioning
confidence: 99%